2019
DOI: 10.1155/2019/4593174
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Hemodynamic Analysis in Cardiovascular Diseases Investigation of Energetic Characteristics of Adult and Pediatric Sputnik Left Ventricular Assist Devices during Mock Circulation Support

Abstract: The need to simulate the operating conditions of the human body is a key factor in every study and engineering process of a bioengineering device developed for implantation. In the present paper, we describe in detail the interaction between the left ventricle (LV) and our Sputnik left ventricular assist devices (LVADs). This research aims to evaluate the influence of different rotary blood pumps (RBPs) on the LV depending on the degree of heart failure (HF), in order to investigate energetic characteristics o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 29 publications
(35 reference statements)
0
5
0
Order By: Relevance
“…For heart function assessment, the most critical parameters monitored were heart rate, cardiac output, ejection fraction, fractional area change, and fractional shortening. Ischemic stroke, atherosclerosis, myocardial ischemia, hypertension, valvular heart disease, heart failure, and rheumatic heart diseases are some angiogenesis-dependent diseases closely related to abnormal hemodynamics (Pugovkin et al, 2019). Bevacizumab, Nintedanib, Pazopanib, Cediranib, Trebananib, and Sorafenib are some of the well-established compounds with anti-angiogenic properties.…”
mentioning
confidence: 99%
“…For heart function assessment, the most critical parameters monitored were heart rate, cardiac output, ejection fraction, fractional area change, and fractional shortening. Ischemic stroke, atherosclerosis, myocardial ischemia, hypertension, valvular heart disease, heart failure, and rheumatic heart diseases are some angiogenesis-dependent diseases closely related to abnormal hemodynamics (Pugovkin et al, 2019). Bevacizumab, Nintedanib, Pazopanib, Cediranib, Trebananib, and Sorafenib are some of the well-established compounds with anti-angiogenic properties.…”
mentioning
confidence: 99%
“…HVAD pump flow ( Q VAD ) was measured by a flow meter at the outflow tube (PXL Clamp-on Tubing Flow sensor ME10PXL-Transonic-ts410). Finally, the cardiac power ( CP ) of the HVAD was calculated with the following formula 17 :…”
Section: Methodsmentioning
confidence: 99%
“…Control issues of the LVAD presented in Figure 2 include: (1) The discrepancy between the parameters that need to be controlled ensuring circulatory support (i.e., P 1 , P 2 , Q 1 , Q 3 ); (2) the parameters generated by the continuous-flow rotary pump (H, Q 2 ); and (3) the parameters that can be tracked and changed in real-time during LVAD support (I, ω). It was previously shown that there are ways to find correlations between different parameters using: (1) A ratio between the maximum flow acceleration and flow pulsatility at baseline pump speed as an alternative to a regression coefficient between the maximum flow acceleration and flow pulsatility at different pump speeds [25]; (2) the external work of the ventricle expressed by the area inside the P-V diagrams which correlates with the area inside dynamic H-Q curves [26]; or (3) energetic characteristics of LV-LVAD interaction [27]. Our hypothesis is that changes in the work (A) of the left ventricle affect the recorded parameter of the electric current (I).…”
Section: Correlation Between Cvs and Pump Parametersmentioning
confidence: 99%